Plasma ceramide, a real-time predictive marker of pulmonary and hepatic metastases response to stereotactic body radiation therapy combined with irinotecan. Issue 2 (May 2016) - Dubois, Nolwenn; Rio, Emmanuel; Ripoche, Natacha; Ferchaud-Roucher, Véronique; Gaugler, Marie-Hélène; Campion, Loic; Krempf, Michel; Carrie, Christian; Mahé, Marc; Mirabel, Xavier; Paris, François
Abstract: Background and purposes: Early biomarkers of tumour response are needed to discriminate between responders and non-responders to radiotherapy. We evaluated the ability of ceramide, a bioactive sphingolipid, to predict tumour sensitivity in patients treated by hypofractionated stereotactic body radiation therapy (SBRT) combined with irinotecan chemotherapy. Materials and methods: Plasma levels of total ceramide and of its subspecies were measured before and during treatment in 35 patients with liver and lung oligometastases of colorectal cancer included in a phase II trial. Cer levels were quantified by LC–ESI-MS/MS and compared to tumour volume response evaluated one year later by CT-scan. Results: Pretreatment plasma ceramide levels were not indicative of tumour response. Nevertheless, the levels of total ceramide and of its 4 main subspecies were significantly higher at days 3 and 10 of treatment in objective responders than in non-responders. According to Kaplan–Meier curves, almost complete tumour control was achieved at 1 year in patients with increased total ceramide levels whereas 50% of patients with decreased levels experienced an increase in tumour volume. Conclusions: Total plasma ceramide is a promising biomarker of tumour response to SBRT combined with irinotecan that should enable to segregate patients with high risk of tumour escape.